Winterreise op. 89 di Schubert: una lettura a tre chiavi (Materiali di Estetica. Terza serie, 2022)
This paper explains the “birth” and development of an idea of performance: “Winterreise” by Franz Schubert; the concert was premiered at Levanto Music Festival (La Spezia-Italy) in summer 2021. The performers were Mirella Di Vita (soprano), Tiziana Canfori (pianist) and Simone Fareri (painter and sculptor). The artists conceived a detailed performance that combined music, lyrics and fine arts, intending to get the audience more involved in listening to this long and complex Lieder cycle. The different languages and the space-time arrangement had to be considered in the structure of this concert to create a more natural and complete sharing experience for the audience.
Keywords: Musical Journey; Concerted with Fine Arts; Counterpoints